Plant-based proteins and their multifaceted industrial applications. (15th January 2022) - Kumar, Manoj; Tomar, Maharishi; Punia, Sneh; Dhakane-Lad, Jyoti; Dhumal, Sangram; Changan, Sushil; Senapathy, Marisennayya; Berwal, Mukesh K.; Sampathrajan, Vellaikumar; Sayed, Ali A.S.; Chandran, Deepak; Pandiselvam, R.; et al.
Abstract: Proteins serve as an imperative macronutrient in human nutrition and well-being. Their nutritional quality substantially varies with their digestibility, amino acid profile, bioavailability, processing and purity. From a nutritional viewpoint, the ideal integration of proteins from diverse plant sources can supply an adequate amount of essential amino acids to fulfil human health needs. The use of plant-derived proteins has recently gained momentum due to their multifaceted edible and nonedible applications and their biodegradable nature. The use of plant proteins will be essential when animal-derived proteins fail to satisfy the requirements of the global population. Physicochemical properties, structural properties, amino acid composition and functional attributes of plant-based proteins are of great interest to the food and processing industries. This review presents various applications of plant-based proteins as food supplements in human nutrition, edible coating materials for fruits and vegetables, emulsifiers in numerous food products, sources of bioactive peptides in nutra- and pharmaceutical products, hydrogels in drug delivery and nonedible applications as wood adhesives. Distinct biological properties of proteins obtained from plant sources such as peanuts, soybeans, kidney beans, rice, quinoa, sunflowers, cottonseed, camelina, maize and others are also conceptually discussed based on their diverse applications in human health and nutrition. Highlights: Application of plant-based proteins is outlined in the review. Edible use of plant proteins (supplement, emulsifier) is discussed. Application of plant proteins in edible coatings/films is highlighted. Plant proteins hydrogels as nutrient delivery agent is discussed. Non-edible application of plant protein is also presented in the review.